Case Report: Laryngeal web in a Yorkshire Terrier - Louie, Nicole; Acosta, Daniel Navarro; Yeadon, Russell; Bęczkowski, Paweł M. (Frontiers in Veterinary Science, 2025)
The laryngeal web is a congenital or acquired, abnormal transverse membrane, most commonly between the free edges of the vocal cords. Ensuing glottic stenosis may be asymptomatic or, in some cases, can lead to vocal and respiratory signs, such as dysphonia, stridor, and dyspnoea. Here, we describe a rare case of a laryngeal web in a Yorkshire Terrier presented with atypical clinical signs, including dysphonia, flatulence, and halitosis. Following a reasonable exclusion of an initial concern of laryngeal neoplasia and given the diagnosis of a congenital laryngeal web, the owners elected not to pursue surgical treatment. The dog’s clinical signs remained unchanged with no development of new respiratory signs for over 4 years post-diagnosis. The findings presented herein highlight the importance of considering the laryngeal web as a rare but possible differential diagnosis for dysphonia and emphasise the need to establish specific individual selection criteria for surgical and medical treatments for dogs affected with this laryngeal anomaly.